2017
DOI: 10.1016/j.jecp.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic influences among childhood shyness, social competences, and cortical responses to emotions

Abstract: Visual event-related potentials (ERPs) evoked by facial expressions are useful to map socioemotional responses among shy children and to predict transition into social phobia. We investigated the sources of covariation among childhood shyness, social competences, and ERPs to other children's happy, neutral, and angry expressions. Electrophysiological and twin analyses examined the phenotypic and etiological association among an index of childhood shyness, an index of social competences, and ERP responses to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Detection of the N170 was typically within timeframes of 140−240 ms, however Battaglia et al (2017) reported a latency of 115.18 ms. As expected, there was a tendency for studies including younger samples, such as Curtis and Cicchetti (2011) , to record wider N170 time windows (up to 300 ms). Examining N170 activity was primarily achieved by utilizing posterior temporal electrodes (T5, T6, P7, P8), however Battaglia et al (2017) recorded N170 using Cz. The selected electrodes seemed dependent upon the age of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detection of the N170 was typically within timeframes of 140−240 ms, however Battaglia et al (2017) reported a latency of 115.18 ms. As expected, there was a tendency for studies including younger samples, such as Curtis and Cicchetti (2011) , to record wider N170 time windows (up to 300 ms). Examining N170 activity was primarily achieved by utilizing posterior temporal electrodes (T5, T6, P7, P8), however Battaglia et al (2017) recorded N170 using Cz. The selected electrodes seemed dependent upon the age of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the average amplitudes recorded ranged from -11.44 μV ( Battaglia et al, 2007 ) to 11.48 μV ( Dennis et al, 2009 ). Sample size ranged from 12 ( Wong et al, 2008 ) to 200 ( Battaglia et al, 2017 ), with a median of 29 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations